GmWRKY49, a Salt-Responsive Nuclear Protein, Improved Root Length and Governed Better Salinity Tolerance in Transgenic Arabidopsis - Xu, Zhaolong; Raza, Qasim; Xu, Ling; He, Xiaolan; Huang, Yihong; Yi, Jinxin; Zhang, Dayong; Shao, Hong-Bo; Ma, Hongxiang; Ali, Zulfiqar (Frontiers in plant science, 2018)
Plant WRKY transcription factors (TFs) are active guardians against pathogens' insurgency, key components in developmental processes, contributors in signal transduction pathways, and regulators of diverse biotic and abiotic stress responses. In this research, we isolated, cloned, and functionally characterized a new WRKY TF GmWRKY49 from soybean. GmWRKY49 is a nuclear protein which contains two highly conserved WRKY domains and a C H -type zinc-finger structure. The normalized expression (log ratio) of was 2.75- and 1.90-fold in salt-tolerant and salt-susceptible soybean genotypes, respectively. The transcripts of could be detected in roots, stems, leaves, flowers, and almost no expression in pod tissues. The salinity-tolerance response of this gene was studied through overexpression in soybean composite seedlings and transgenic . The effect of overexpression on root length of transgenic was also investigated. Under salt stress, several parameters including germination rate, survival rate, root length, rosette diameter, relative electrolyte leakage, and proline content were significantly higher in composite seedlings and transgenic than those in wild-type. Moreover, enhanced salinity tolerance in soybean mosaic seedlings and transgenic . These results suggest that is a positive regulator of salinity tolerance in soybean and has high potential utilization for crop improvement.